2011
DOI: 10.1111/j.1399-0012.2010.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor screening algorithm for exclusion of thrombophilia during evaluation of living donor liver transplantation

Abstract: Living donor liver transplantation (LDLT) has evolved based on the premise that donor safety is most important. In 2005, we encountered a donor who developed a pulmonary embolism during the early post-operative period. As it is important for donors to be healthy, most risk factors related to perioperative thrombosis, such as obesity, age, and malignancy are used as exclusion criteria during the evaluation process. We speculated that thrombophilia not detected by conventional laboratory examinations may cause p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The best clinical practice for the time being is a full investigation for the possibility of inherited coagulation disorders, followed by careful monitoring of the postoperative coagulation profile both in donors and recipients . The routine use of elastic stockings, early postoperative ambulation, and careful consideration of central venous line placement in the borderline coagulation profile group are also beneficial …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best clinical practice for the time being is a full investigation for the possibility of inherited coagulation disorders, followed by careful monitoring of the postoperative coagulation profile both in donors and recipients . The routine use of elastic stockings, early postoperative ambulation, and careful consideration of central venous line placement in the borderline coagulation profile group are also beneficial …”
Section: Discussionmentioning
confidence: 99%
“…(27) The routine use of elastic stockings, early postoperative ambulation, and careful consideration of central venous line placement in the borderline coagulation profile group are also beneficial. (28) Nine potential donors with hypercoagulability risks were excluded in our series. Six cases were related to a low level of protein S or protein C. Kitchens et al reported a successful LT with a graft from a donor with low protein S level.…”
Section: Discussionmentioning
confidence: 99%
“…Given this context, several authors have recommended that routine thrombophilia screening (screening for protein C, protein S, AT deficiency, APCR and prothrombin mutation) be conducted before liver transplantation so as to prevent the transmission of prothrombotic abnormalities from the donor to the recipient (17). Furthermore, thrombophilia patients have occasionally been excluded as living donor candidates in an effort to avoid donor thrombosis occurring during the perioperative period (18).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, patients with coagulopathies or thrombophilias have been disqualified as liver donors, due to the risk to the donor from their underlying condition and the risk of transmitting these blood disorders to the transplant recipient, as most clotting factors and thromboregulatory proteins are predominantly produced in the liver [8,9]. Indeed, donor-to-recipient transmission of factor VII [12], factor XI [13], factor XII [14], protein C [15] and protein S deficiency [10] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, estimates from several case series conclude that 2.4-3.8% of patients with spontaneous VTE have deficient protein S activity [6,7]. As protein S is predominantly (although not exclusively) produced in the liver, protein S deficiency in a donor has traditionally been an absolute contraindication for liver transplantation [8,9]. Indeed, symptomatic acquired protein S deficiency resulting from liver transplantation utilizing a graft obtained from a deceased donor has been described [10].…”
Section: Introductionmentioning
confidence: 99%